(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to investigate the impact of the LEAD strategy on teamwork skills among second-year intermediate school students in government day schools. Umm Al-Mu’minin School, affiliated with the First Education Directorate of Al-Koura/Qom Abi Urayb, was intentionally selected as the research site for the academic year (2026-2025). The researcher selected one of two classes as the experimental group, which studies according to the LEAD strategy, and the other as the control group, which studies according to the traditional method. The two research groups were compared in a number of variables, including (chronological age in months, intelligence test, prior knowledge, and a teamwork skills scale). The results showed that the two groups were equivalent. The research methodology used was the teamwork skills scale from the study (Weng, 2000), which includes three main skills divided into three sections and thirty items. After administering the scale, statistically significant differences were found at the (0.05) level between the mean scores of the three students in the experimental group who studied according to the LEAD strategy and the mean scores of the three students in the control group who studied according to the traditional method, in favor of the latter The experimental group, and in light of this, a set of recommendations and conclusions and suggestions were developed.